The synthetic α-bromo-2',3,4,4'-tetramethoxychalcone (α-Br-TMC) inhibits the JAK/STAT signaling pathway. - Sophia Pinz; Samy Unser; Susanne Brueggemann; Elisabeth Besl; Nafisah Al-Rifai; Hermina Petkes; Sabine Amslinger; Anne Rascle (PLoS ONE)
Signal transducer and activator of transcription STAT5 and its upstream activating kinase JAK2 are essential mediators of cytokine signaling. Their activity is normally tightly regulated and transient. However, constitutive activation of STAT5 is found in numerous cancers and a driving force for malignant transformation. We describe here the identification of the synthetic chalcone α-Br-2',3,4,4'-tetramethoxychalcone (α-Br-TMC) as a novel JAK/STAT inhibitor. Using the non-transformed IL-3-dependent B cell line Ba/F3 and its oncogenic derivative Ba/F3-1*6 expressing constitutively activated STAT5, we show that α-Br-TMC targets the JAK/STAT pathway at multiple levels, inhibiting both JAK2 and STAT5 phosphorylation. Moreover, α-Br-TMC alters the mobility of STAT5A/B proteins in SDS-PAGE, indicating a change in their post-translational modification state. These alterations correlate with a decreased association of STAT5 and RNA polymerase II with STAT5 target genes in chromatin immunoprecipitation assays. Interestingly, expression of STAT5 target genes such as Cis and c-Myc was differentially regulated by α-Br-TMC in normal and cancer cells. While both genes were inhibited in IL-3-stimulated Ba/F3 cells, expression of the oncogene c-Myc was down-regulated and that of the tumor suppressor gene Cis was up-regulated in transformed Ba/F3-1*6 cells. The synthetic chalcone α-Br-TMC might therefore represent a promising novel anticancer agent for therapeutic intervention in STAT5-associated malignancies.